The effects of an entomopathogenic fungus, Beauveria bassiana (Balsamo) Vuillemin (Hyphomycetes), on Prostephanus truncatus (Horn) (Col: Bostrichdae), Sitophilus zeamais (Col: Curculionidae) and grain losses in stored maize in the Benin Republic - Meikle, W.G.; Cherry, A.J.; Holst, N.; Hounna, B.; Markham, R.H. (Elsevier, 2001)
A fungal entomopathogen, Beauveria bassiana, was used to treat maize ears placed in traditional grain stores against Prostephanus truncatus in a field experiment conducted from September 1997 to March 1998 in the Benin Republic, West Africa. Treatments included oil-based spray with and without conidia, maize stored with and without the husk, and stores with and without artificial infestation. Additional treated ears kept in insect-proof cages under field conditions were sampled weekly and exposed to insects to estimate the virulence and persistence of the pathogen during the storage season. P. truncatus densities were significantly lower in treatments that included conidia, although densities were high in all artificially infested treatments and grain losses were severe. The effect of the pathogen was modeled with an exponential decay function and incorporated in a published P. truncatus simulation model. The effects of hypothetical pathogens with different virulence and persistence characteristics were evaluated in terms of insect density and percentage grain loss.